Sociocultural care in practicality: in search of care that makes sense - Maria de Lourdes Denardin Budó (Universidad de Alicante, 2016)
The author deals with the importance of linking nursing and anthropology for being possible a care which is appropriated to the people perspectives, especially regarding to those with chronic illnesses. Thus, the care should make sense to people, making it essential to approach professional and popular knowledges for a dialogue searching for a satisfactory care.